2019
DOI: 10.1038/s41598-019-53798-8
|View full text |Cite
|
Sign up to set email alerts
|

Barley grain (1,3;1,4)-β-glucan content: effects of transcript and sequence variation in genes encoding the corresponding synthase and endohydrolase enzymes

Abstract: The composition of plant cell walls is important in determining cereal end uses. Unlike other widely consumed cereal grains barley is comparatively rich in (1,3;1,4)-β-glucan, a source of dietary fibre. Previous work showed Cellulose synthase-like genes synthesise (1,3;1,4)-β-glucan in several tissues. HvCslF6 encodes a grain (1,3;1,4)-β-glucan synthase, whereas the function of HvCslF9 is unknown. Here, the relationship between mRNA levels of HvCslF6, HvCslF9, HvGlbI (1,3;1,4)-β-glucan endohydrolase, and (1,3;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…To assess the distribution of (1,3;1,4)‐β‐glucan in WT grain compared with lines carrying induced mutations, we used immunolabelling with the BG1 antibody (Burton et al ., 2011). Developmental stages for analysis were selected based on the transcript abundance of the target genes; for HvCslF6 , we sampled mature grain; and for HvCslF9 , we sampled grain at 15 DPA, as this follows the peak of expression of this gene (Burton et al ., 2008; Garcia‐Gimenez et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the distribution of (1,3;1,4)‐β‐glucan in WT grain compared with lines carrying induced mutations, we used immunolabelling with the BG1 antibody (Burton et al ., 2011). Developmental stages for analysis were selected based on the transcript abundance of the target genes; for HvCslF6 , we sampled mature grain; and for HvCslF9 , we sampled grain at 15 DPA, as this follows the peak of expression of this gene (Burton et al ., 2008; Garcia‐Gimenez et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…HvCslF9 expression in developing grain is generally low but shows a prominent peak at about 8 DPA (cv. Sloop; Burton et al ., 2008), although this varies depending on the cultivar (Garcia‐Gimenez et al, 2019). In cv.…”
Section: Discussionmentioning
confidence: 99%
“…The MLG content was reported to account for 20% of the total dietary fiber content in wheat (Prasadi and Joye, 2020). Wirkijowska et al (2012) reported that the content of (1-3) (1-4)-β-D-glucans in barley kernel ranged between 4.04 and 5.71% of dry matter, and Garcia-Gimenez et al (2019) expressed that barley has a considerably higher MLG content (4-10%) compared with wheat (1%) or rice (<0.06%), although (Fincher, 2009a) reported that (1-3) (1-4)-β-D-glucans constitute up to 70% of starchy endosperm in barley. In all these reports, the amount of MLG was measured in a few samples/accessions.…”
Section: Discussionmentioning
confidence: 99%
“…Β-glucan constitutes approximatively 75% of dry weight of endosperm cell walls, and arabinoxylan constitutes 25% [ 75 ]. The percentages of beta-glucan content in the barley grain vary according to the different polymorphisms of the genes that encode the corresponding synthase and endohydrolase enzymes [ 76 ]. Barley β-glucans also have cholesterol-lowering properties [ 77 , 78 ], however, lower than oats [ 79 ].…”
Section: Cerealsmentioning
confidence: 99%